Estudo comparativo do uso de métodos do diagnóstico por imagem no ensino da anatomia humana na formação do tecnólogo em radiologia. - Feitoza, Alonso Átila Pires (2019)
The teaching of Human Anatomy (AH) in the Superior Course of Technology (CST) in Radiology is fundamental for the training of the professional of the area. Without this knowledge, it is impossible to adequately read the image of the human body in complementing the plans and diagnoses of pathologies. The results of the National Student Performance Examination (Enade) in this course, in Brazil, in the last cycles (2007 to 2016), denote students' unsatisfactory performance in AH content. The insufficient and continuous performance of the students in the Enade, inquires about the methodology used in the discipline Human Anatomy in the CST in Radiology. This study aims to evaluate the perceptions and performance of CST students in Radiology before and after the use of imaging methods associated with Human Neuroanatomy (NH). It is, therefore, an action research, with the intervention of courses of improvement with and without the use of image, in groups (control and experimental). The research universe is composed of students of the CST in Radiology of the State of Ceará and the samples are 46 students. To evaluate the perceptions, an adaptation to the questionnaire, Student Evaluation Educational Quality (SEEQ) was used. The results demonstrate that students agree that the teaching of Human Anatomy is better understood when associated with imaging methods, with an overall rate of 4.9 on a Likert scale of five categories. In order to evaluate performance, statistical inferences were made by means of parametric and non-parametric hypothesis tests. Regarding performance, both groups had averages well below the acceptable mean (5.5) determined at the beginning of the study, with a mean of 1.45 and a standard deviation (SD) of 0.58 for the control group and for the group experimental group of 1.65 with SD of 0.88, revealing low proficiency in Human Neuroanatomy. Interventions were able to modify students' learning reality, where the control group obtained a mean of 4.17 SD of 1.69. The experimental group, using an alternative methodology, with the use of digital resources and methods of image diagnosis, obtained a better performance with a mean of 5.69 and SD of 1.88. Statistical tests show that the experimental group performed better at the end of the training course.